2010
DOI: 10.1111/j.1365-2230.2009.03360.x
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the association between diet and occurrence of acne: a rational approach from a traditional Chinese medicine perspective

Abstract: The application of a TCM approach led to the detection of significant associations between diet and the incidence of acne.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 17 publications
2
9
1
Order By: Relevance
“…Similar with our study, Law et al in their cross-sectional study performed in 2009 on 322 participants aged 17.4-20.8 years, reported negatively association between dairy consumption and acne occurrence [40]. Although most studies conducted to date claim milk as the main factor that aggravates acne, there are still insufficient data to rec-ommend restricting milk consumption in acne treatment.…”
Section: Comparative Analysis Of Our Data With the Previously Reportedsupporting
confidence: 89%
“…Similar with our study, Law et al in their cross-sectional study performed in 2009 on 322 participants aged 17.4-20.8 years, reported negatively association between dairy consumption and acne occurrence [40]. Although most studies conducted to date claim milk as the main factor that aggravates acne, there are still insufficient data to rec-ommend restricting milk consumption in acne treatment.…”
Section: Comparative Analysis Of Our Data With the Previously Reportedsupporting
confidence: 89%
“…This would contradict the finding by Law et al. 1 that in the yin‐predominant patients, a higher intake of yang‐rich food was associated with a lower likelihood of acne.…”
contrasting
confidence: 77%
“…I read with interest the recent article by Law et al. 1 in Clinical and Experimental Dermatology . As a general practitioner with dual training in western and Traditional Chinese Medicine (TCM), I pay due respect to the hypothesis of diet as a causative reason for acne.…”
mentioning
confidence: 99%
“…Jung JY, et al 28 Cross the control group, aged 17.4-20.8, it was reported that dessert and juice triggered AV. 29 Karadağ et al reported that white sugar, dairy products, ice cream and white bread may increase acne severity. On the other hand, an inverse proportion was reported between whole wheat bread, fish, and legumes and acne development.…”
Section: Case Control a Total Of 3826 Acne Vulgaris Patients And 759 mentioning
confidence: 99%